2021
DOI: 10.12659/msm.932731
|View full text |Cite
|
Sign up to set email alerts
|

miRNA Profiling of Hungarian Regressive Wilms’ Tumor Formalin-Fixed Paraffin-Embedded (FFPE) Samples by Quantitative Real-Time Polymerase Chain Reaction (RT-PCR)

Abstract: Background Wilms’ tumor is a common renal malignancy of early childhood with a generally favorable prognosis depending upon histological subtype. It is becoming increasingly clear that differences in miRNA (microRNA) expression signature represent important clues helping us predict a tumor’s response to chemotherapy. In our study, we aimed to reveal miRNAs deregulated in regressive Wilms’ tumors from FFPE (formalin-fixed, paraffin-embedded) samples, also showing whether such samples are reliable m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
(64 reference statements)
2
5
0
1
Order By: Relevance
“…In this context, miR-200b-3p has been identi ed to be associated with metastatic WT [35], and our results indicate that miR-200b-3p is a potential universal WT miRNA. Recent studies have reported interesting results regarding the downregulation of miR-184 and miR-194-5p in both regressive and blastemal tumors [24,25]. Our ndings support these results for differentially expressed miRNAs, but put the identi ed miRNAs in the context of universal and ubiquitous markers of WT.…”
Section: Discussionsupporting
confidence: 85%
“…In this context, miR-200b-3p has been identi ed to be associated with metastatic WT [35], and our results indicate that miR-200b-3p is a potential universal WT miRNA. Recent studies have reported interesting results regarding the downregulation of miR-184 and miR-194-5p in both regressive and blastemal tumors [24,25]. Our ndings support these results for differentially expressed miRNAs, but put the identi ed miRNAs in the context of universal and ubiquitous markers of WT.…”
Section: Discussionsupporting
confidence: 85%
“…88 Bugly o et al observed that lower expression of miR-203a in Wilms' tumor (WT) tissues has prognostic value for cancer development. 90 Further, the downregulation of miR-203a in primary melanoma 94 serves as a potential biomarker for metastatic cutaneous melanoma (MCM). 86 A study on intracranial ependymoma shows that increased expression of miR-203a was correlated with grade III tumors and could assist as a prognostic and diagnostic marker for ependymoma.…”
Section: Mir-203a In Prognosis and Diagnosis Of Cancermentioning
confidence: 99%
“…Infection of the Hepatitis‐C virus suppresses the expression of miR‐203a and increases EMT in HCC cell lines, so the loss of miR‐203a marks a poor prognosis 88 . Buglyó et al observed that lower expression of miR‐203a in Wilms' tumor (WT) tissues has prognostic value for cancer development 90 . Further, the downregulation of miR‐203a in primary melanoma 94 serves as a potential biomarker for metastatic cutaneous melanoma (MCM) 86 .…”
Section: Mir‐203a In Prognosis and Diagnosis Of Cancermentioning
confidence: 99%
“…1/8000 gyermek, így Magyarorszá gon durván 6-8 Wilmstumort lehet diagnosztizálni évente [62]. A daganat nőkben kissé gyakoribb, és az esetek 10-15%a társul daganatszindrómákhoz, amelye ket pontmutációk, deletiók, epigenetikai módosulások hoznak létre, viszont Wilmstumorokban megfigyelték már a mikroRNSek eltéréseit is [62][63][64]. Az utóbbiak biomarkerként használva akár a terápiás választ is elő jelezhetik [65].…”
Section: Wilms-tumorunclassified